Nutritional evaluation of corn and sorghum crop residues - R.K. Taylor; Gary L. Kilgore; James J. Higgins; Dale A. Blasi; Stewart R. Duncan (Kansas Agricultural Experiment Station Research Reports, 1999)
Crop residue samples from 22 grazed and nongrazed corn and sorghum residue fields across Kansas were collected every 2 weeks during the 1997/98 winter feeding season to evaluate quality and yield. Corn residue averaged about 2 ½ tons of total dry matter (DM)/acre, with the leaf fraction (attached and unattached) constituting about 60% of that residue. Unattached leaves represented 85% of the total leaf DM. Yield estimates for sorghum residue averaged over 2 tons/ acre. The stem component represented 55 to 60% of the total DM collected, and about 58% of the leaves remained attached to the stem.
Keywords: Cattlemen& #x27; s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Crop residues; Forage quality